Efficacy of entomopathogenic nematode (Heterorhabditis indica) in controlling phorid Fly, Megaselia sandhui in Agaricus bisporus - Lamba, J S; Mrig, K K; Singh, S (Mushroom Research, 2015)
Please see the full text